2018
DOI: 10.1177/2150135118775413
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Defined by Fluid Corrected Creatinine in Neonates After the Norwood Procedure

Abstract: Acute kidney injury is common after the Norwood procedure. Correcting creatinine for fluid balance revealed new cases of AKI. Use of an mBTS and higher VIS on POD 0 were associated with increased risk of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
1
23
0
2
Order By: Relevance
“…Many earlier studies reported that longer CPB duration was a major risk factor for AKI, conferring up to 7 times greater odds if CPB duration was greater than 180 minutes (4,11). Contrarily, a lack of association between CPB duration and AKI has been found by several other groups (15,25,26). The association seen only in 1 of the 3 surgeries could be because of cross-clamp time, as CPB duration was only significant in the setting of longer cross clamp times.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many earlier studies reported that longer CPB duration was a major risk factor for AKI, conferring up to 7 times greater odds if CPB duration was greater than 180 minutes (4,11). Contrarily, a lack of association between CPB duration and AKI has been found by several other groups (15,25,26). The association seen only in 1 of the 3 surgeries could be because of cross-clamp time, as CPB duration was only significant in the setting of longer cross clamp times.…”
Section: Discussionmentioning
confidence: 97%
“…The association between AKI and higher VIS in the early post-operative period is likely a marker of illness severity (26,28). Garcia et al evaluated a cohort of adolescents and found that VIS was a predictor of worse outcomes (composite of death, cardiopulmonary resuscitation, mechanical circulatory support, arrhythmias, infection, acute neurologic injury and stage 3 AKI), but they did not specifically evaluate the association between AKI and higher VIS (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the priming volume of the bypass circuit used, a neonate's volume of distribution may be increased 8-40% through the use of CPB and thus the decrease in sCr may be dilutional. Moreover, post-operative fluid shifts and the need for intravascular volume repletion are common and might impact sCr measurement [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…28 Fluid overload is a ubiquitous clinical entity that has been associated with prolonged mechanical ventilation, length of stay, and mortality. [29][30][31][32][33][34][35][36] However, the timing, degree, and association with acute kidney injury and other risk factors are poorly understood. Certainly, acute kidney injury contributes to fluid overload but not all neonates with acute kidney injury have fluid overload and not all neonates with fluid overload have acute kidney injury or oligo-anuria.…”
Section: Fluid Overloadmentioning
confidence: 99%